(untitled) (Research, Society and Development, 2021)
The objective was to elaborate the hygienic-sanitary profile of an Institutional Food and Nutrition Unit (UAN) through the evaluation of the use of Good Manufacturing Practices (GMP) before and after the implementation of quality tools. Therefore, a checklist was used to carry out descriptive research on hygienic-sanitary conditions and to assess whether the GMP are efficient or not. The study also evaluated the microbiological contamination of equipment, utensils, environment, water, handlers’ hands and food preparations after implementing quality tools. This work sought to identify flaws in the process and thus propose improvements in order to obtain guidelines aimed at safe production. There were improvements in the hygienic-sanitary profile evidenced by the change in classification from group 2 (fair) to group 1 (good) motivated by the implementation of quality tools focused on corrective measures. In microbiological analyses, satisfactory standards were observed for water and air quality in the environment, the analysis of mesophilic aerobics in equipment and utensils indicated that 50% of the samples presented values higher than the recommendations. Hands of handlers showed absence of thermotolerant coliforms and Staphylococcus aureus. For all foodstuffs studied, no contamination by Staphylococcus aureus and Salmonella sp. However, thermotolerant coliform microorganisms were identified in raw kale salad. It is concluded that the implementation of quality tools contributed positively to the production of safe food and helps to identify failures and decision making; such tools need careful vigilance to maintain results.